SIX PILLARS OF GLOBAL FOOD SECURITY IN INDONESIA: A SYSTEMIC LITERATURE REVIEW - M. Fauzan 'Azhima; Shannaz Mutiara Deniar; Tubagus Chaeru Nugraha; Salahudin Salahudin (Universitas Padjadjaran, 2023)
Indonesia’s national food security is still in an unstable condition. Indonesia is currently a food-importing country. Therefore, the purpose of this study is to describe the six pillars of global food security in Indonesia. To achieve the objectives of this study, a systematic literature review method was used. The data used were 254 scientific articles sourced from the Scopus database. To review the articles, the Vosviewer application was used. The results of the study reveal that food availability, food access, food utilization, food stability, food agency, and food sustainability are the six main pillars that must exist in every country to support their food security. This research contributes to two main things. First, the description of the six pillars of food security contributes to the development of the roadmap of Food Security. Second, the description of the six pillars of food security acts as the direction of Indonesia’s food policy. However, in this study, the articles used were only sourced from the Scopus and Mendeley databases, so the findings of this study have not comprehensively described the issue of the six pillars of global food security in Indonesia. Future research needs to use scientific articles sourced from other reputable international databases, such as the Web of Science and Pilaronds Scholars.